Spotlight on nature : tips and techniques for drawing and painting nature on location - Hein, Virginia; Wong, Gail L. (Urban sketching handbook ;, 2022)
The Urban Sketching Handbook: Spotlight on Nature demonstrates how to make the most of nature in on-location drawings and paintings.